Palliative laparoscopic resection of renal cell carcinoma metastatic to the stomach: report of a case - Costa, Thiago Nogueira (World J Surg Oncol, 2014)
The most common sites of metastases in renal cell carcinoma (RCC) are lung and bone. However, unusual sites, including the stomach, are characteristic of RCC. This article presents a case of a metastatic RCC (lung and liver) with a symptomatic gastric metastasis treated by a laparoscopic wedge resection (LWR). A 66-year-old woman, diagnosed with RCC underwent a right nephrectomy. During her follow-up, an upper gastrointestinal (GI) endoscopy showed an ulcerated lesion at the stomach. A biopsy of the specimen revealed metastatic RCC. The patient underwent a palliative LWR and was discharged home 8 days after surgery. Therefore, LWR is a relatively simple technique with the advantages of minimal invasive access in the treatment of palliative cases.